The Impact of Economic Growth on Environmental Pollution: The Case of Uzbekistan - Muminova Elnorakhon A.; Usmanov Akramjon A.; Akhunova Shokhistakhon N.; Askarov Farhod R.; Mamasadikov Abror A. (E3S Web of Conferences, 2024)
This article examines the relationship between economic development and environmental pollution in Uzbekistan using the Environmental Kuznets Curve (EKC) model. The main attention is paid to the analysis of the dynamics of emissions of pollutants into the atmosphere depending on indicators of economic activity, such as gross domestic product (GDP) per capita and coal consumption. To evaluate the data, the methods of correlation and regression analysis were used. The results of the study show that there is an inverse relationship between the level of economic development and the degree of environmental pollution after reaching a certain level of per capita income. The findings highlight the need to correctly account for environmental costs in economic policy and provide recommendations for improving the environmental situation in the country in the context of achieving sustainable development goals.